Kesehatan Gigi Mulut dan Pemanfaatan Pelayanan Kesehatan Gigi Mulut pada Ibu Hamil (Studi Pendahuluan di Wilayah Puskesmas Serpong, Tangerang Selatan) - Rani Anggraini; Peter Andreas (Majalah Kedokteran Gigi Indonesia, 2015)
Oral Health and Dental Visit of Pregnant Women (Pilot Study in Serpong, South Tangerang). Pregnancy has a significant effect on oral health-related hormonal changes, diet and behavior. Pregnant women become very susceptible to gingival and periodontal disease. Oral health condition of pregnant women may adversely bring impacts such as preterm low birth weight (PLBW). The aim of this study is to gain an overview of oral health status, knowledge and use of dental care service in pregnant women. This was a descriptive study with cross sectional approach. The structured interviews involved 34 pregnant women in Puskesmas Serpong. The questions included the characteristics of the respondents, oral health care practice, problem related to oral health during pregnancy, oral health knowledge and dental health service utilization in pregnant women. Chi-squares test were conducted to examine bivariable relationships between sociodemographic, oral health status and knowledge to dental health services utilization. The results show that more than half of pregnant woman respondents (52.94%) descibed their oral health as good and 61.8% did not have any dental health problems. As many as 55.9% of the respondents had knowledge about the importance of oral dental health during pregnancy. Only about 35.5% of the respondents visited dentists in the last one year. There is a significant correlation between dental health problem and dental health knowledge of pregnant women to the use of dental health services. The conclusion from this study is that dental health problem in pregnant women affects the utilization of dental care during pregnancy and is associated with the knowledge about dental health during pregnancy.